Characterization of a gene family encoding SEA (sea-urchin sperm protein, enterokinase and agrin)-domain proteins with lectin-like and heme-binding properties from Schistosoma japonicum. - Evaristus Chibunna Mbanefo; Mihoko Kikuchi; Nguyen Tien Huy; Mohammed Nasir Shuaibu; Mahamoud Sama Cherif; Chuanxin Yu; Masahiro Wakao; Yasuo Suda; Kenji Hirayama (Public Library of Science (PLoS), 2014)
BACKGROUND: We previously identified a novel gene family dispersed in the genome of Schistosoma japonicum by retrotransposon-mediated gene duplication mechanism. Although many transcripts were identified, no homolog was readily identifiable from sequence information. METHODOLOGY/PRINCIPAL FINDINGS: Here, we utilized structural homology modeling and biochemical methods to identify remote homologs, and characterized the gene products as SEA (sea-urchin sperm protein, enterokinase and agrin)-domain containing proteins. A common extracellular domain in this family was structurally similar to SEA-domain. SEA-domain is primarily a structural domain, known to assist or regulate binding to glycans. Recombinant proteins from three members of this gene family specifically interacted with glycosaminoglycans with high affinity, with potential implication in ligand acquisition and immune evasion. Similar approach was used to identify a heme-binding site on the SEA-domain. The heme-binding mode showed heme molecule inserted into a hydrophobic pocket, with heme iron putatively coordinated to two histidine axial ligands. Heme-binding properties were confirmed using biochemical assays and UV-visible absorption spectroscopy, which showed high affinity heme-binding (K D = 1.605×10(-6) M) and cognate spectroscopic attributes of hexa-coordinated heme iron. The native proteins were oligomers, antigenic, and are localized on adult worm teguments and gastrodermis; major host-parasite interfaces and site for heme detoxification and acquisition. CONCLUSIONS: The results suggest potential role, at least in the nucleation step of heme crystallization (hemozoin formation), and as receptors for heme uptake. Survival strategies exploited by parasites, including heme homeostasis mechanism in hemoparasites, are paramount for successful parasitism. Thus, assessing prospects for application in disease intervention is warranted.